2013
DOI: 10.1159/000354236
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction Occurs prior to Clinical Evidence of Polycystic Kidney Disease

Abstract: Objective: Polycystic kidney disease (PKD), a monogenic disease with an autosomal dominant or an autosomal recessive form of inheritance (ARPKD), is the most common genetic cause of renal dysfunction and end-stage renal failure. In addition to the development of cysts, the autosomal form of PKD is associated with vascular endothelial dysfunction, a marker of vascular disease. Whether vascular endothelial dysfunction is also present in ARPKD, and its relationship with renal dysfunction remain to be determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(28 reference statements)
0
18
0
2
Order By: Relevance
“…Indeed, endothelial dysfunction is an early and potentially reversible manifestation of atherosclerosis, with multifactorial etiology [52-54], and it develops in ADPKD patients, preceding the renal failure [55-56]. Atherosclerosis has been considered to play a key role in the early phases of cardiovascular disease found in ADPKD [57-59]. Cardiopulmonary exercise testing is considered the gold-standard for assessment of cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endothelial dysfunction is an early and potentially reversible manifestation of atherosclerosis, with multifactorial etiology [52-54], and it develops in ADPKD patients, preceding the renal failure [55-56]. Atherosclerosis has been considered to play a key role in the early phases of cardiovascular disease found in ADPKD [57-59]. Cardiopulmonary exercise testing is considered the gold-standard for assessment of cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, vascular dysfunction in ADPKD is related to endothelial function (FMD) and potentially atherosclerosis (cIMT) more than to fluid overload (PWV) or cardiac failure (echocardiography). We [16, 17] and others [18, 19] have previously reported an impaired vascular function during early-stage ADPKD in cross-sectional studies and single modalities assessing vascular functions, while Peterson et al [20] studied endothelium-dependent vasodilation in a rat model of ADPKD and reported changes there that preceded a rise in mean arterial pressure or drop in GFR. With the present data, these findings are extended and broadened, demonstrating the consistent nature of ADPKD vasculopathy (early onset, FMD worse than cIMT, which in turn is worse than PWV and precedes any changes in cardiac geometry) as well as the extent to which vascular decline precedes that of GFR and also develops at a faster rate.…”
Section: Discussionmentioning
confidence: 99%
“…Karen et al have found that the aorta in an autosomal recessive ARPKD animal model had abnormal endothelium-dependent vascular reactivity, likely due to a primary defect in the endothelial cells that occurred prior to the changes in mean arterial pressure or renal function. However, the endothelium-independent relaxation, for example, that in smooth muscle cells, was not impaired [19] .…”
Section: Trpp2's Function In Endothelial Cellsmentioning
confidence: 91%
“…Mutation of the PKD2 gene is a major cause of autosomal dominant polycystic kidney disease (ADPKD), which is a common genetic disease of the kidney [18] . However, patients with ADPKD suffer from not only a defect in kidney function but also a systemic disorder associated with abnormalities in the vasculature, such as cerebral, intracranial, and aortic aneurysms and cardiac valvular dysfunction [19][20][21] . Therefore, cardiovascular complications are typically the leading cause of mortality and morbidity in ADPKD patients [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%